PERSEPSI PENYULUH DAN PETANI TERHADAP PENTINGNYA PERAN PENYULUHAN PERKEBUNAN KOPI ARABIKA DI KECAMATAN PURBA KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Hengki F Sidauruk; Eri ' Sayamar; Kausar ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purposes of this research about the agricultural extension field and farmer perceptions for importance the role of extension Arabica Coffee plantations in Purba District Simalungun Regency North Of Sumatera Province is: 1. To determind the organizing of extension Arabica Coffee. 2. To determind the agricultural extension field perceptions for the importance the role of extension arabica coffee plantations. The method taked of data used is a survey method. Sample in the research is extension field and farmer, intake of agricultural extension field  respondents with census method amount 10 people and intake of farmer respondents with purposive sampling with considering 4 chosen villages whose numbers of farmers are the highest and chosing 2 villages that was trained by a civil-servant trainer, selecting 10 people of each village. The number of farmers chosen as samples in total is 60 farmers of total 14 villages. They are members of farmer groups with consideration on number of members and the status of the group. Data analysis uses a Scale Likert’s Summated Rating (SLR). Variables used in this research is by comparing those of Mardikanto and Law No. 16 of  2006 as many as 9 variables. The results of this study are that organizing of extension in Purba District has been carried out well in accordance with counselling elements. Counseling has a perceptions the role of extension Arabica Coffee plantations gives an average score of 3.94 with an “Important” category. While the farmers’ perception gives an average score of 4.01 with an “Important” category.   Keywords: Perceptions, Agricultural Extension Field, Farmers, The Importance ofRole  Extension